Stock Market Performance and GDP Growth in Nepal: Evidence from ARDL Bounds Testing and Granger Causality Analysis - Bhandari, Khimananda (Tribhuvan University Journal, 2026)
This study examines the relationship between stock market performance and economic growth in Nepal using annual time-series data from 1994 to 2024. It addresses the finance-growth nexus in the context of Nepal’s developing and relatively less mature capital market. The study analyzes both long and short-run dynamics between GDP growth and selected stock market and macroeconomic indicators, including market capitalization, the number of listed companies, interest rates, and inflation. The Autoregressive Distributed Lag (ARDL) bounds testing approach is employed to examine long-run cointegration, while the Error Correction Model (ECM) is used to assess short-run adjustment. Granger causality tests are also applied to identify the direction of causality among the variables. The empirical results confirm a statistically significant long-run equilibrium relationship among the variables. The interest rate and the number of listed companies have positive and statistically significant effects on long-run GDP growth. In the short run, inflation has a significantly negative effect. The negative sign of the error-correction term indicates adjustment toward the long-run equilibrium. The results also reveal bidirectional causality between stock market development and economic growth, while interest rate and inflation show mixed but significant conditional effects. The findings suggest that stock market development contributes to Nepal’s economic growth, but this relationship depends on macroeconomic stability. The study highlights the need to deepen capital markets, strengthen regulation, and maintain stable inflation and interest rate conditions.